17 Alpha Hydroxyprogesterone Caproate (17OHPC) vs Nifedipine as a Maintenance Tocolytic after Arrested Preterm Labor - Nigar, Asma; Hakim, Seema; Mohsin, Zehra (Medical Research and Its Applications Vol. 2, 2024)
Background: Preterm birth remains a major cause of concern in obstetrics. It can result in poor neonatal outcomes in neonates because of various complications of prematurity like intraventricular hemorhage, necrotizing enterocolitis, respiratory distress, sepsis, severe neurological deficit and neonatal death. For decades, progesterone has been studied in different preparations and doses to decrease preterm delivery, especially in those with high-risk factors like multiple pregnancies, short cervix, prior preterm deliveries etc. 17 alpha hydroxyprogesterone caproate is a synthetic derivative of 17 alpha hydroxyprogesterone, that has shown to reduce recurrent preterm birth before 37 weeks. This study was done to evaluate the efficacy of 17 alpha hydroxyprogesterone caproate, in preventing preterm delivery after acute tocolysis with nifedipine in patients with preterm labor irrespective of the risk factors for preterm delivery. Material & Methods: It was a prospective clinical trial that was carried out on 100 pregnant females between 28-34 weeks of gestation diagnosed with preterm labor. All patients in preterm labor were given nifedipine for acute tocolysis and antenatal corticosteroid was given to all patient for lung maturity. After tocolysis, undelivered patients were randomly allocated to case (n=50) and control group (n=50). Patients in case group were given 17 alpha hydroxyprogesterone caproate,250 mg, through intramuscular route, weekly and continued till 36 weeks of gestation or delivery, which ever occurred earlier. Patients in control group were given nifedipine as a maintenance tocolytic as and when required. Results were analyzed in terms of gestational age at delivery and neonatal outcome in both groups. Results and Discussion: The mean gestational age at delivery was 35.2±2.3 weeks in the case group and 35.4±2.6 weeks in the control group. It was statistically similar in the two groups. Neonatal outcome was also found to be statistically similar in both groups. Conclusion: This study suggests that patients with preterm labor, arrested by tocolytics can be given 17 alpha hydroxy progesterone caproate as a maintenance tocolytic as a suitable alternative to nifedipine.